Effective Treatment of Glioblastoma Multiforme With Oncolytic Virotherapy: A Case-Series - Gesundheit, Benjamin; Ben-David, Eliel; Posen, Yehudit; Ellis, Ronald; Wollmann, Guido; Schneider, E. Marion; Aigner, Karl; Brauns, Lars; Nesselhut, Thomas; Ackva, Ingrid; Weisslein, Christine; Thaller, Arno (Frontiers in Oncology, 2020)
Glioblastoma multiforme (GBM) remains an incurable condition, associated with a median survival time of about 15 months with best standard of care and 5-year survival rate of <10%. We report on four GBM patients on combination treatment regimens that included oncolytic virus (OV) immunotherapy, who achieved clinical and radiological responses with long-time survival thus far up to 14 years and good quality of life. We discuss the radiological findings that provide new insights into this treatment, the scientific rationale of this innovative and promising therapy, and considerations for future research.